The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.25115/ejrep.v17i49.2650
|View full text |Cite
|
Sign up to set email alerts
|

El uso de tecnologias de la información y comunicación como estrategia motivacional en el aula mixta

Abstract: El uso de tecnologías de la información y comunicación como estrategia motivacional en el aula mixta Resumen Introducción. El actual desempeño académico y ante las exigencias del mundo profesional, es indispensable el fortalecimiento del saber Ser, entendiéndose como el sentirse competente y autónomo, a partir de un ambiente sustentador utilizando dentro de las aulas las tecnologías para el aprendizaje y el conocimiento, por lo tanto, el objetivo de la presente investigación fue analizar la motivación y el sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In a publication comparing learning and information literacy achievements among Thai student groups [56], it was found that students using blended learning understood the content better and enjoyed their increased autonomy. Other authors also reported students' appreciation of autonomy and intrinsic motivation [58]. In a pilot study with physical therapy and medical students [57], the blended learning model was more effective than the face-to-face method for teaching practices related to chronic patient care.…”
Section: Model Comparisonmentioning
confidence: 95%
See 1 more Smart Citation
“…In a publication comparing learning and information literacy achievements among Thai student groups [56], it was found that students using blended learning understood the content better and enjoyed their increased autonomy. Other authors also reported students' appreciation of autonomy and intrinsic motivation [58]. In a pilot study with physical therapy and medical students [57], the blended learning model was more effective than the face-to-face method for teaching practices related to chronic patient care.…”
Section: Model Comparisonmentioning
confidence: 95%
“…Regardless of course content, most of these research projects indicated that blended learning models led to better student success compared to traditional teaching [55][56][57][58][59]. In a publication comparing learning and information literacy achievements among Thai student groups [56], it was found that students using blended learning understood the content better and enjoyed their increased autonomy.…”
Section: Model Comparisonmentioning
confidence: 99%